How can virtual production be used to create flexible and modular pipelines for short film and music video creation? : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Creative Enterprise at Massey University, Wellington, New Zealand - Williams, Thomas (Massey University, 2023)
Virtual Production encompasses a selection of emerging techniques and technologies for audio visual content creation. Virtual Production requires a large depth of knowledge in order to be implemented into production pipelines. This thesis explores various virtual production tools and techniques through the generation of multiple creative projects, including short films and music videos. The goal of this research is to explore the research question: How can Virtual Production be used to create Flexible and Modular Pipelines for Short Film and Music Video Creation. This question will be explored through the development of various pipelines for a wide variety of creative projects. The effectiveness of these pipelines is evaluated through three key metrics: flexibility, modularity and cost-effectiveness. Using a practice-led research methodology, flexibility, modularity and cost-effectiveness are evaluated through the completion of multiple subsequent creative projects. Each subsequent project builds on the knowledge gained from the previous project, allowing the knowledge gained to accumulate. This research project contributes to the Virtual Production landscape by providing an insight into how Virtual Production can be implemented into multiple different projects to enhance the creative process, with a particular emphasis on small-scale and small-budget projects, of which there is currently limited literature.
Keywords: 360505 Screen media